Economic Analysis On Design Of A Simple Hydraulic Reaction Type Turbine For Low-Head Low-Flow Pico Hydro - Md Basar, Mohd Farriz; Mohd Rais, Nurul Ashikin; Ibrahim, Khairul Anwar; Mohd Hassan, Fatin Syakira; Sopian, Kamaruzzaman (Blue Eyes Intelligence Engineering & Sciences Publication (BEIESP), 2019)
The purpose of this paper is to establish a techno-economic analysis on the design of a new Z-Blade turbine focusing on problems of costing and manufacturing process which focus on a low-head and low-flow pico hydro. Pico hydro generation system with a capacity less than 5kw has been gaining increasing attention as preferred methods of clean power generation. Accordingly, the design and operating procedures as well as economic analysis for a Z-Blade reaction type turbine are described in detail. Furthermore, the constructive analysis of the literature on the simple reaction type water turbine are discuss through quantitative summarization, classification, costing and comparison. In this paper also, will re-evaluated the manufacturing process of the SRT and CPT based on techno-economic analysis and the disadvantages of both turbines are identified. Meanwhile, the additional features of Z-Blade will be investigated under low-head low-flow water resources with simple geometrical design and low fabrication cost. Ideally, this hydro generation system is inexpensive and has a simple fabrication method with costing estimation at only USD76, which comprises 7.6% of total cost of hydro-electric installation and capable of producing mechanical power up to 115W under low-head and low-flow water resources